PARTISIPASI PEREMPUAN DALAM KONSERVASI MANGROVE DI DESA PASAR BANGGI KABUPATEN REMBANG - Cahyani Pratisti; Hery Saksono; Suadi Suadi (Jurnal Perikanan Universitas Gadjah Mada, 2012)
This research was aims to determine the form, level and the factors affecting women’s participation in mangrove conservation at Pasar Banggi Village, Rembang District. Survey was conducted on respondents with total number of 95 people, comprised of 50 women, 14 men, 10 children and 25 people representing related agencies were interviewed with semi-open questionnaire. The study showed that there were nine forms of female participation in conservation activities, which was women who are looking for information, planting seeds, fi ll polybags, nursery planning, decision-making in the implementation of the nursery, nurture the seeds of mangrove, mangrove preserve, transfer of knowledge to children and warn if there is people cut the tree. Based on Arnstein (1969) participation ladder, the study showed that female participation rates ranging from therapy to the partnership. Factors that affect women in conservation were women’s perceptions of themselves, social status and public perception of women’s participation. Women play an important role in the cycle of mangrove conservation, especially in the nursery stage. Nevertheless, women have not been involved in the decision-making process and enjoy the sale of mangrove seedlings. Strengthening women’s bargaining power and involvement in the management group is required to enable the equality of access and control between men and women in a cycle of mangrove conservation. This research was aims to determine the form, level and the factors affecting women’s participation inmangrove conservation at Pasar Banggi Village, Rembang District. Survey was conducted on respondentswith total number of 95 people, comprised of 50 women, 14 men, 10 children and 25 people representingrelated agencies were interviewed with semi-open questionnaire. The study showed that there were nineforms of female participation in conservation activities, which was women who are looking for information,planting seeds, fi ll polybags, nursery planning, decision-making in the implementation of the nursery,nurture the seeds of mangrove, mangrove preserve, transfer of knowledge to children and warn if thereis people cut the tree. Based on Arnstein (1969) participation ladder, the study showed that femaleparticipation rates ranging from therapy to the partnership. Factors that affect women in conservationwere women’s perceptions of themselves, social status and public perception of women’s participation.Women play an important role in the cycle of mangrove conservation, especially in the nursery stage.Nevertheless, women have not been involved in the decision making process and enjoy the sale ofmangrove seedlings. Strengthening women’s bargaining power and involvement in the managementgroup is required to enable the equality of access and control between men and women in a cycle ofmangrove conservation.